Unstructured PEEC method with the use of surface impedance boundary condition. Issue 5 (20th May 2020) - Meunier, Gerard; Phan, Quang-Anh; Chadebec, Olivier; Guichon, Jean-Michel; Bannwarth, Bertrand; Torchio, Riccardo
Abstract : Purpose: This paper aims to study unstructured-partial element equivalent circuit (PEEC) method for modelling electromagnetic regions with surface impedance condition (SIBC) is proposed. Two coupled circuits representations are used for solving both electric and/or magnetic effects in thin regions discretized by a finite element surface mesh. The formulation is applied in the context of low frequency problems with volumic magnetic media and coils. Non simply connected regions are treated with fundamental branch independent loop matrices coming from the circuit representation. Design/methodology/approach: Because of the use of Whitney face elements, two coupled circuits representations are used for solving both electric and/or magnetic effects in thin regions discretized by a finite element surface mesh. The air is not meshed. Findings: The new surface impedance formulation enables the modeling of volume conductive regions to efficiently simulate various devices with only a surface mesh. Research limitations/implications: The propagation effects are not taken into account in the proposed formulation. Originality/value: The formulation is original and is efficient for modeling non simply connected conductive regions with the use of SIBC. The unstructured PEEC SIBC formulation has been validated in presence of volume magnetic nonconductive region and compared with a SIBC FEM approach. The computational effort is considerably reduced in comparison with volume approaches.